2016
DOI: 10.15288/jsad.2016.77.277
|View full text |Cite
|
Sign up to set email alerts
|

Other- and Self-Directed Forms of Violence and Their Relationship With Number of Substance Use Disorder Criteria Among Youth Ages 12–17: Results From the National Survey on Drug Use and Health

Abstract: ABSTRACT. Objective: The purpose of this study was to examine the associations between the number of substance use disorder (SUD) criteria as listed in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and other-and self-directed forms of violence among youth ages 12-17 in the general population. Method: Data were obtained from the National Survey on Drug Use and Health pooled across survey years 2008-2013, with a combined sample of 108,560 respondents ages 12-17. Violence categories d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We identified 18 eligible studies (for details, see Figure 1 and Table 1 ) that included 591,411 individuals with drug use disorders. Studies were from 5 countries: 14 from the United States ( n = 542,393, 91.7%) ( 53 , 54 , 56–67 ) and 1 each from New Zealand ( n = 182, 0.03%) ( 68 ), Denmark ( n = 43,403, 7.3%) ( 69 ), the Netherlands ( n = 5,303, 0.9%) ( 70 ), and Turkey ( n = 130, 0.02%) ( 71 ). Eight studies used case–control designs ( 53 , 54 , 56 , 58 , 63 , 66 , 67 , 71 ); the remaining 10 studies were longitudinal cohorts with a median follow-up of 9.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified 18 eligible studies (for details, see Figure 1 and Table 1 ) that included 591,411 individuals with drug use disorders. Studies were from 5 countries: 14 from the United States ( n = 542,393, 91.7%) ( 53 , 54 , 56–67 ) and 1 each from New Zealand ( n = 182, 0.03%) ( 68 ), Denmark ( n = 43,403, 7.3%) ( 69 ), the Netherlands ( n = 5,303, 0.9%) ( 70 ), and Turkey ( n = 130, 0.02%) ( 71 ). Eight studies used case–control designs ( 53 , 54 , 56 , 58 , 63 , 66 , 67 , 71 ); the remaining 10 studies were longitudinal cohorts with a median follow-up of 9.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…For outcome measurement, 2 studies used violent conviction from official records ( 65 , 69 ) and 1 reported intimate partner violence from the partner’s report ( 62 ). Most used self-report items in the Diagnostic Interview Schedule ( 56 ), PPC Delinquency and Criminal Behavior inventory ( 57 ), Aggression Questionnaire ( 58 ), Conflict Tactics Scale ( 63 ), physical aggression subscale in Buss-Perry Scale ( 71 ), and specially developed questionnaires ( 53 , 54 , 60 , 61 , 66 , 67 , 70 ). A combination of several measures (e.g., official records and self-report) was applied in 3 studies ( 59 , 64 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations